Exploring approaches to overcome challenges in adopting human resource analytics through stakeholder engagement - Alam S; Dong Z; Kularatne I; Rashid MS (Springer Nature Switzerland AG, 2025)
As modern enterprises increasingly turn to data-driven decision-making, human resource management (HRM) has also embraced the potential of human resource analytics (HRA) to optimize talent management and gain a competitive edge. However, adopting HRA in practice presents challenges across data governance, technical, and organizational domains. This systematic review, synthesizing insights from 110 studies, identifies key obstacles and practical strategies to address them. Recommendations include fostering a data-driven culture, enhancing training and development, and promoting team collaboration. By tackling these challenges, HR professionals can unlock the full potential of HRA, transforming HRM into a strategic driver of organizational success.
Keywords: Human resource analytics; Human resource management; Data-driven decision-making; Stakeholder